Opinion Polls and the Media
XV, 291 p.
Keywords: Opinion Polls and the Media provides the most comprehensive analysis to date on the relationship between the media, opinion polls, and public opinion. Looking at the extent to which the media, through their use of opinion polls, both reflect and shape public opinion, it brings together a team of leading scholars and analyzes theoretical and methodological approaches to the media and their use of opinion polls. The contributors explore how the media use opinion polls in a range of countries across the world, and analyze the effects and uses of opinion polls by the public as well as political actors.